The implementation of electroforming technology on home industry and souvenir center in Malang - Budiono Budiono; Suwarsono Suwarsono; Trihono Sewoyo (Universitas Ahmad Dahlan, 2023)
Souvenir industry is the supporting aspect of tourism industry. As the one of creative economy industries, souvenir shows the characteristics of a region or a tourism place. This industry needs expertise and creativity, but there is an issue in the development of product variations with high expenses and the improvement of skills to create a product. The method to conduct this program is by conducting empowerment with participative and bottom-up approach. The participants are given electroforming training for souvenir industry. From the implementation of this program, the souvenir industry is given assistance through the training of electroforming technology to improve their creativity and souvenir production.Souvenir industry is the supporting aspect of tourism industry. As the one of creative economy industries, souvenir shows the characteristics of a region or a tourism place. This industry needs expertise and creativity, but there is an issue in the development of product variations with high expenses and the improvement of skills to create a product. The method to conduct this program is by conducting empowerment with participative and bottom-up approach. The participants are given electroforming training for souvenir industry. From the implementation of this program, the souvenir industry is given assistance through the training of electroforming technology to improve their creativity and souvenir production.